Formulation Stocks Gel Toothpaste Essential Oil Basil ( Ocimum Basilicum L. ) And Test ActivitiesAntibacterials Against Bacteria Streptococcus Mutanss - Pratiwi, Febrina Ramadhika nur Indah; , Dr. T.N. saifullah S., M.Si., Apt; , Ratna Yuliani, M. Biotech. St (2016)
Streptococcus mutans plays a role in the formation of dental plaque which results in tooth surface demineralization. Continuously demineralization cause cavities. Essential oil of basil (Ocimum basilicum L.) with linalool content inhibits the growth of S. mutans. Basil essential oil is formulated in toothpaste gel to facilitate its use. The purposes of this study were to determine physical properties, antibacterial activity, and stability of toothpaste gel containing basil essential oil. Essential oil concentration used in the preparation of toothpaste gel was 12.5% v/v. Toothpaste gels with concentration ratio of carbopol 934 and tween 80 of 0.5 : 1.5 (F1), 1 : 2 (F2), 1.5 : 0.5 (F3) dan 2 : 1 (F4) were made. Organoleptic test, viscosity, pH, dispersive power, the size of the globules, and antibacterial activity of toothpaste gel were tested. Normally distributed data that were statistically analyzed using One-Way Anova test, while the data were not normally distributed were analyzed using the Kruskal-Wallis test. The results showed that increase concentrations of carbopol 934 and decrease in the concentration of tween 80 increased the viscosity and decreased dispersive power significantly. In addition, variations in the concentration of carbopol 934 and tween 80 affect the antibacterial activity of toothpaste gel formulation basil essential oil. Stability studies showed that toothpaste gel F4 with 2% carbopol 934 and 1% tween 80 was the most stable in storage and freeze thaw cycling test.